Keswadayaan Petani dalam Pengelolaan Sumberdaya Air untuk Irigasi (Forum Penelitian Agro Ekonomi, 2016)
EnglishThe improvement of efficiency in using water irrigation needs a comprehensive and sistematic approach. Unfortunately, the applied approach was biased to technical aspect and especially focused on management in the resource base and at aggregate levels. Referring to those approach, the improvement of institution were develop by using top-down mechanism, very rigid incline to be homogenous and it caused over cooptation to the local institution which is had a capability in applying an efficient and sustain water irrigation management Finally, the efficiency in using water irrigation at farmer level is difficult to create. The reformulation approach to develop institution by give a big priority to farmer self reliance is required to develop a better water irrigation management IndonesianPeningkatan efisiensi pemanfaatan air irigasi membutuhkan pendekatan sistematis dan komprehensif. Pendekatan yang diterapkan selama ini bias kepada aspek teknis dan terfokus pada pengelolaan di tingkat sumberdaya dan agregat. Pengembangan kelembagaan dilakukan secara "top-down", sangat formal, cenderung homogen, dan mengakibatkan terjadinya kooptasi berlebihan terhadap kelembagaan lokal yang sesungguhnya memiliki kapabilitas untuk mewujudkan sistem pengelolaan irigasi yang efisien dan berlanjut. Pada akhirnya hal itu menyebabkan efisiensi penggunaan air irigasi di tingkat petani sulit diwujudkan. Reformulasi strategi dan pendekatan yang cocok untuk mewujudkan sistem kelembagaan yang memberikan bobot lebih besar kepada peran keswadayaan petani diharapkan dapat memperbaiki sistem pengelolaan irigasi.